Fabrication parameters affecting the thermal conductivity of polymer-based thermal interface material - Razonado, Ivy Ann C. (College of Engineering, University of the Philippines Diliman, 2018)
In the recent years with our fast-changing technology, goals of producing gadgets are now more focused on efficiency and miniaturization. However, with these requirements come greater challenges on the design in the chip level, particularly in the heat dissipation. Semiconductor industries addressed this problem with the use of thermal interface materials of which polymer-clay nanocomposites have already been investigated. Previous studies have shown that changes in the processing methods of polymer-clay nanocomposites caused changes on the properties of the polymer from being brittle to pliable after addition of nanoclay up to 5% to 9% by volume; and having a thermal conductivity of ~1 to ~9 W/m-K upon addition of nanoclay of up to 13% by volume. In this study, the aim was to obtain a satisfactory thermal conductivity (for polymer matrix composites ~1-5W/m-K) at a lower addition of nanoclay by modifying the microstructure in the polymer-clay nanocomposite that may be induced by the different parametric settings in the mixing process and casting techniques. The UP-MMT nanocomposites were fabricated by solution intercalation followed by two different techniques of casting, i.e. mold casting and tape casting. To facilitate the dispersion of nanoclay filler in the polymer matrix, high-power ultrasonication was employed under various parametric settings. Results showed that the sample with the highest thermal conductivity coefficient of 2.873 W/m-K was obtained from the composite with 5% by volume filler loading and dispersed at sonication parameters of 80% pulse rate, 50% power and 15 mins sonication time. This thermal conductivity is equivalent to that of the 9% by volume filler loading when sonication was not applied and filler was mixed manually. The effective sonication parameters were then used to prepare samples for the determination of the effect of casting techniques on the microstructure and thermal conductivity of the nanocomposites. Results showed only a slight increase of about 4% in the thermal conductivity coefficient of the tape casted samples at 2.993 W/m-K compared to the mold casted samples. Nevertheless, this thermal conductivity is already equivalent to that of the 11% by volume filler loading when sonication was not applied, filler was mixed manually and samples were mold casted. TEM micrographs showed that nanocomposites produced from both casting methods exhibited a dispersed microstructure however tape casted samples exhibited smaller agglomerations of nanoclay at ~280 nm compared to ~320 nm for the mold casted samples. Both methods also exhibited an intercalated microstructure wherein the d spacing between the nanoclay platelets have been increased from 2.48 nm to 2.88 nm for mold casting method, and from 2.48 nm to 2.96 nm for tape casting method. The higher increase observed in the tape casted samples are thought to be due to the infusion of the polymer in between the platelets induced by the applied shear force during casting. Further, based on the high magnification TEM micrographs, it can also be said that the tape casted samples showed nanoclay particles oriented in a certain direction that may be associated to the blading direction and the corresponding applied shear stress of about 2.11 Pa, which was estimated from the viscosity of the nanoclay - polymer suspension and shear rate during tape casting. The resulting preferred orientation may have shortened the distances between nanoclay fillers and effectively lowering the heat transfer through polymer-rich regions. Given these microstructure modifications, it can therefore be said that the slight increase in the thermal conductivity coefficient of the tape casted samples may be attributed to the modified microstructure induced by tape casting. Moreover, sonication at specific parametric combination induced the highest increase in thermal conductivity owing to the significant dispersion in the microstructure. Polymer-based thermal interface material (UP-MMT) fabricated in this study reached the coefficient thermal conductivity requirement used in semiconductor applications.